Pengembangan Multimedia Interaktif Berbasis Articulate Storyline pada Pembelajaran Tematik Abad 21 bagi Siswa Sekolah Dasar - Itsnaaini Nur Halimah; Fitri Indriani (Universitas Negeri Malang, 2021)
The use of interactive multimedia in the 21st-century era in learning is necessary to enable students to develop various skills, especially 21st-century skills. This research aims to produce interactive multimedia products based on articulate storylines on the thematic understanding of the 21st century for elementary school students. This type of research is Research and Development with ADDIE (Analysis, Design, Development, Implementation, Evaluation) research model. A team of experts assess the product quality test: material experts, media experts, learning experts, and linguists, assessments from teachers, and student response questionnaires. The evaluation results have obtained as follows; Material expert assessment results in 90 (very good), media experts 90 (very good), learning experts 85 (very good), linguists (good), teacher ratings 95 (very good), and student response 84 (excellent). The average score of the evaluation results is 86.04, thus, the product can be declared worthy as a medium and support learning with the category